Prototype Design of Business Performance Assessment of Tenants Independent Entrepreneurship Program Using the EFQM Model - Maulana, Danis; Afrianto , Afif Zuhri; Al Hakimy, M. Robith Silahul Islam Mush’ Ab; Arif, Muhammad Lukman (Jurnal Entrepreneur dan Entrepreneurship, 2023)
Additionally, the Independent Entrepreneur Program (WMK) at Shipbuilding Institute of Polytechnic Surabaya (PPNS) organizers have not yet had a well-integrated information system to effectively and efficiently gather information for business performance assessments of the tenants. This research aims to develop a prototype of the Information System for Business Performance Assessment of WMK PBLT PPNS tenants using the European Foundation for Quality Management (EFQM) model. The result of this research is a prototype of the Information System for Business Performance Assessment of WMK PBLT PPNS tenants. Based on the EFQM assessment, the average total business performance assessment score obtained is 897, with the highest category being “Orientation on Integrated Quality Management” with a ratification score >800-1000. That indicates that the businesses run by the tenants have achieved optimal performance results. With this prototype, it is hoped to assist in the process of assessing tenant business performance more effectively and efficiently.